2008
DOI: 10.1029/2008gl034476
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineral reactions caused by frictional heating during an earthquake: An example from the Taiwan Chelungpu fault

Abstract: [1] To understand the chemical reactions of clay minerals in a fault zone during an earthquake, we analyzed the clay minerals in the Chelungpu fault, which slipped during the 1999 Chi-Chi earthquake. X-ray diffraction spectroscopy showed that kaolinite and smectite contents were lower in the black gouge zone than in the surrounding gray gouge, breccia, or fracture-damaged zones. We applied a chemical kinetics approach to examine whether dehydroxylation of kaolinite and dehydration of interlayer water, dehydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 21 publications
5
61
1
1
Order By: Relevance
“…These results suggest that the transformation of Ca-smectite into illite has progressed in the fault gouge. It has been proposed that the transformation of smectite to illite in the shear zone occurs by dissolution and recrystallization processes, shear-related deformations, and frictional heating (Yan et al 2001;Hirono et al 2008;Casciello et al 2011). The coexistent anomalies of R o and the clay mineralogy anomalies in the gouges suggest that frictional heating is the most likely cause for the illitization within the gouges (Yamaguchi et al 2011b).…”
Section: Earthquake Faulting Recorded In Fault Gougesmentioning
confidence: 99%
“…These results suggest that the transformation of Ca-smectite into illite has progressed in the fault gouge. It has been proposed that the transformation of smectite to illite in the shear zone occurs by dissolution and recrystallization processes, shear-related deformations, and frictional heating (Yan et al 2001;Hirono et al 2008;Casciello et al 2011). The coexistent anomalies of R o and the clay mineralogy anomalies in the gouges suggest that frictional heating is the most likely cause for the illitization within the gouges (Yamaguchi et al 2011b).…”
Section: Earthquake Faulting Recorded In Fault Gougesmentioning
confidence: 99%
“…The composition of natural fault gouges also shows complex variation: Many gouges consist largely of clay minerals such as smectite and illite (e.g., Vrolijk and van der Pluijm 1999;Hirono et al 2008a;Lockner et al 2011), although sandy gouge has been reported in the major thrust in the Nankai Trough (Hirono et al 2014a). Because understanding the role of microscale deformation structure (fabrics) and mineralogy in fault gouges is important for developing process-based models of friction, many experimental studies have been performed (e.g., Ikari et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the mechanisms are activated by frictional heating during 1 rapid slip characteristic of seismic events, including thermal pressurization of pore fluids (TP), flash heating of the microscopic contacting asperities, and frictional melting [e.g., Rice, 2006, and references therein]. The temperature rise in the vicinity of a fault has been studied based on geological observations, including the existence of pseudotachylytes [e.g., Sibson, 1975], the change in the ESR signal [Fukuchi et al, 2005], the decomposition and reaction of rock-forming minerals [e.g., Hirono et al, 2008;Hamada et al, 2009aHamada et al, , 2009b, and the recovery of fission tracks [d'Alessio et al, 2003]. It is critically important to incorporate frictional heating and the resulting weakening processes into models of earthquake sequences so that the seismological observations as well as outcomes from field and experimental geology can be properly interpreted.…”
Section: Introductionmentioning
confidence: 99%